Theme of Wine and Wine Drinking in Late Medieval Transoxiana Sufism in 16th Century - Yuzmukhametov, Ramil Tagirovich; Ismoilov, Lutfullo Eshonovich; Rajabova, Markhabo Tukhtasunovna (International Journal of Criminology and Sociology, 2022)
The article is devoted to wine drinking in the Sufi sources of Transoxiana of the 16th century, on the example of Manakibs. The importance of research on this topic lies in determining wine drinking in the secular and religious traditions of Muslim society. Besides, the topic's relevance is due to the insufficient study of the issues of semantic interpretation of the concept of wine in Sufi writings. Hence, this article aims to disclose the various meanings of the concept of wine contained in Sufi writings. The primary method in the study of this issue is the historical and comparative method, and the method of literary analysis, which allows creating a holistic view of the hidden images of wine in the Sufi writings of Maverannahr of the 16th century. It is known that wine, winemaking, and wine drinking for many centuries, despite strict Islamic prohibitions, were present in Muslim society, as evidenced by historical chronicles, literary works. This phenomenon also applies to the history of the State of the Timurids and Sheibanids, where winemaking and wine drinking were widely practiced among representatives of different sectors of society.